ChemInform Abstract: Silicon Acceleration of a Tandem Alkene Isomerization/Electrocyclic Ring‐Opening of 2‐Methyleneoxetanes to α, β‐Unsaturated Methylketones. Issue 15 (15th April 2014) - Farber, Elisa; Rudnitskaya, Aleksandra; Keshipeddy, Santosh; Lao, Kendricks S.; Gascon, Jose A.; Howell, Amy R.
Abstract Heating of methyleneoxetanes is found to result in new, unexpected, and selective formation of methyl vinylketones via oxetene intermediates.